Pengaruh Antara Brand Experience, Brand Authenticity dan Brand Equity Terhadap Customer Satisfaction Pada Generasi Z - Raina Asa Ivadah; Primasatria Edastama (Masyarakat Ekonomi Syariah Bogor, 2026)
Increasing competition in the local sneaker industry requires companies to focus not only on products, but also on brand experience and consumer perceptions in order to enhance customer satisfaction and brand competitiveness. This study aims to analyze the effects of brand experience, brand authenticity, and brand equity on customer satisfaction among local sneaker consumers in the Jabodetabek area. The research employs a quantitative approach using purposive sampling with 105 respondents who are users of local sneaker brands, namely Compass, Ventela, and Aerostreet, in Jabodetabek. Data were collected through a Likert-scale questionnaire and analyzed using Structural Equation Modeling (SEM) with the assistance of SmartPLS 4. The results indicate that brand experience, brand authenticity, and brand equity have positive and significant effects on customer satisfaction. In addition, brand experience plays an important role in shaping brand authenticity and brand equity. These findings suggest that the management of a consistent, authentic, and high-value brand experience is a crucial factor in enhancing customer satisfaction and loyalty toward local sneaker brands. This study provides practical implications for local sneaker companies in designing marketing strategies oriented toward brand experience, authenticity, and brand value, and recommends future research to expand the geographical scope and employ a longitudinal approach to strengthen the generalizability of the findings.